2018
DOI: 10.5664/jcsm.7332
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Adherence to Positive Airway Pressure Therapy and Long-Term Outcomes in Patients With Obesity Hypoventilation Syndrome: A Prospective Observational Study

Abstract: Title: PAP Therapy in Patients With Obesity Hypoventilation Syndrome, Registry: ClinicalTrials.gov, Identifier: NCT03449641, URL: https://clinicaltrials.gov/ct2/show/NCT03449641.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Similar levels of adherence are reported with CPAP and NIV, of 5 to 6 h/night. Previous work has suggested adherence is an important modifiable predictor of hypercapnia in OHS (55,63).…”
Section: Recommendationmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar levels of adherence are reported with CPAP and NIV, of 5 to 6 h/night. Previous work has suggested adherence is an important modifiable predictor of hypercapnia in OHS (55,63).…”
Section: Recommendationmentioning
confidence: 93%
“…Observational studies and RCTs have reported improvements in awake respiratory failure, symptoms, and quality of life to a similar degree in both CPAP-and NIV-treated individuals with OHS (11,20,22,55,58,63,(77)(78)(79)(80). Although CPAP does not increase alveolar ventilation, it can improve awake respiratory failure by facilitating the unloading of CO 2 accumulated during complete or partial airflow obstruction during sleep (81,82).…”
Section: Recommendationmentioning
confidence: 97%
See 1 more Smart Citation
“…Most hospitalizations and deaths in untreated patients with OHS seem to be caused by respiratory complications such as acute-on-chronic respiratory chestjournal.org failure and pulmonary embolism. 11,28,29 However, in cohorts of patients with OHS undergoing long-term NIV therapy, 4,30 and in our long-term results for patients with severe OSA, 55% of the deaths were of cardiovascular etiology. 19 This finding suggests that PAP may reduce morbidity and mortality because of respiratory causes but has less impact on cardiovascular outcomes.…”
mentioning
confidence: 73%
“…This interest is reflected in the studies by Sivam and colleagues and Bouloukaki and colleagues published in this issue of the Journal of Clinical Sleep Medicine. 1,2 Sivam and colleagues investigate the prevalence of isolated nocturnal hypercapnia in obese patients referred to an outpatient sleep unit for suspected sleep-disordered breathing. 1 This study relies on a premise that OHS represents a clinical spectrum, whereby patients with isolated nocturnal hypoventilation may go on to develop daytime hypoventilation.…”
mentioning
confidence: 99%